Wireless hacks - Flickenger, Rob (O'Reilly, 2003)
"Wireless Hacks offers 100 industrial-strength tips about wireless networking, contributed by experts who apply what they know in the real world every day. Inside, you will find a wealth of useful techniques for making the most out of wireless technology, including how to make sense of the alphabet soup of 802.11 standards, and determine which technology is the best fit for your situation; use Bluetooth, mobile radios, mobile data networks, cellular telephones, Wi-Fi hotspots, and other exotic methods to keep you connected, no matter where you are; employ practical methods for detecting, analyzing, and monitoring wireless networks--your own and those available to the public; extend the range of your network, making the best possible use of the availableradio spectrum; design and build your own wireless access points and antennas; survey and engineer long-zdistance network links spanning several miles; and understand the security issues of wireless networking, and protect